Treatment of the Cuban infantile literature in the second cycle of the primary school from the perspective the new technologies - Cristina Rodríguez-Rodríguez (Maestro y Sociedad, 2016)
Toward the ends of the XX century, the society is impacted by the Computer Technologies of the Communications (TIC). Its advantages become palpable in the different spheres of the society. Cuba is not unaware of this reality and it includes as an indispensable factor in its Third Educational Revolution, the incorporation of these. Nevertheless, in the second decade of the XXI century difficulties remain so much in the access, readiness of resources, like in the use form. It is in the solution this last aspect, where the primary teacher plays a fundamental list. This work offers some considerations about the competent use of the Educational Digital Means (MDE) in the treatment of texts of the Cuban Infantile Literature (LIC) in the sixth degree of the Primary Education and demands of a didactic alternative to carry out an use different from those (MDE) in a systematic and renovating way.